2020
DOI: 10.1055/s-0039-1701002
|View full text |Cite
|
Sign up to set email alerts
|

Self-Management Behaviors of Patients with Type 1 Diabetes: Comparing Two Sources of Patient-Generated Data

Abstract: Objectives This article aims to evaluate adult type 1 diabetes mellitus (T1DM) self-management behaviors (SMBs) related to exercise and alcohol on a survey versus a smartphone app to compare self-reported and self-tracked SMBs, and examine inter- and intrapatient variability. Methods Adults with T1DM on insulin pump therapy were surveyed about their alcohol, meal, and exercise SMBs. For 4 weeks, participants self-tracked their alcohol, meal, and exercise events, and their SMBs corresponding with thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 32 publications
0
18
0
1
Order By: Relevance
“…Data interoperability is one of the main drawbacks of deployed solutions/systems where users are "constrained" within one application for a task and move between the applications to view/review the patient information. 19,[39][40][41] Further improvements are required such as adding diet information, ethnicity, location, socioeconomic status, living status, and other social factors that could have a significant influence on the healthy and active lifestyle for managing T2DM and delaying the prediabetes. [2][3][4]27,28 Early Detection of Prediabetes and T2DM Baig et al 7…”
Section: Discussionmentioning
confidence: 99%
“…Data interoperability is one of the main drawbacks of deployed solutions/systems where users are "constrained" within one application for a task and move between the applications to view/review the patient information. 19,[39][40][41] Further improvements are required such as adding diet information, ethnicity, location, socioeconomic status, living status, and other social factors that could have a significant influence on the healthy and active lifestyle for managing T2DM and delaying the prediabetes. [2][3][4]27,28 Early Detection of Prediabetes and T2DM Baig et al 7…”
Section: Discussionmentioning
confidence: 99%
“…10,28 Our previous work in T1DM patients on CSII therapy using both data from a survey in conjunction with self-tracked data collection using a mHealth app indicated a high intra-and interpatient variability of SMBs. 19,20,22,24 Findings on variability of SMBs from the phenotyping algorithms used were discussed in follow-up personalized interventions. Our interviews asked about SMBs and practices discovered in the created SMB reports to manage diabetes when eating, drinking alcohol, and exercising.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, and partly as a result of these challenges, there are scarce data regarding adherence to CSII therapy and SMBs among adults with T1DM, as prior qualitative and quantitative studies have focused primarily on children or young adults. 5,6,[9][10][11][12][16][17][18] While recent evidence shows that there is considerable variability of SMBs within and between adult patients with T1DM on insulin pump therapy who use CSII, [19][20][21][22] current behavioral interventions are mostly based on the "one size fits all" approach of standardized diabetes self-management education. 1 This is unfortunate since individuals are more likely to follow self-management protocols that take their lifestyle preferences into account.…”
Section: Background and Significancementioning
confidence: 99%
See 1 more Smart Citation
“…The most frequently used assessment method was taking a photo of the food, used in out of dietary assessment tools (48.8%). Participants were usually asked to take a picture immediately before eating (21,25,34,35,, but taking a photo was not always mandatory (63,64). In two studies, participants were specifically asked to fit all foods and drinks in one photo (65,66), while one study specifically reported that participants were also able to capture additional foods and drinks while eating (67).…”
Section: Photo-based Assessmentmentioning
confidence: 99%